Engine Testing - Martyr, A. J.; Plint, M. A. (Dublin : Butterworth, Limited, 2007)
Annotation This book brings together the large and scattered body of information on the theory and practice of engine testing, to which any engineer responsible for work of this kind must have access. Engine testing is a fundamental part of development of new engine and powertrain systems, as well as of the modification of existing systems. It forms a significant part of the practical work of many automotive and mechanical engineers, in the auto manufacturing companies, their suppliers suppliers, specialist engineering services organisations, the motor sport sector, hybrid vehicles and tuning sector. The eclectic nature of engine, powertrain, chassis and whole vehicle testing makes this comprehensive book a true must-have reference for those in the automotive industry as well as more advanced students of automotive engineering. * The only book dedicated to engine testing; over 4000 copies sold of the second edition * Covers all key aspects of this large topic, including test-cell set up, data management, dynamometer selection and use, air, thermal, combustion, mechanical, and emissions assessment * Most automotive engineers are involved with many aspects covered by this book, making it a must-have reference
Hard Cover